Social media effectiveness on youth purchasing behaviour of soft drinks in Tanzania: a study of University of Dar es Salaam students - Mbura, Omari K.; Kagoya, Sumaya M. (University of Dar es Salaam Library Journal, 2021)
The article assesses social media effectiveness on youth purchasing behaviour of soft drinks in Tanzania. With the help of the AIDA Model and Media Theory, the article focuses on the content, attitude and awareness of social media as they affect youth purchasing behaviour of soft drinks. A structured questionnaire to gather data was distributed to 80 conveniently sampled non PhD University of Dar es Salaam youth students. More so, 3 purposively selected key informants were interviewed for in-depth information. A mixed method approach was used for data analysis, where quantitative analysis was primarily utilised and complemented by in-depth interviews from key informants. Multiple regression analysis aided by SPSS Version 20 was used to analyse the quantitative data. The findings indicate that of the three constructs, youth purchasing behaviour appears to be positively and significantly influenced by two predictor variables namely, content and awareness of social media constructs. A third construct of attitude towards social media had a positive, but insignificant influence on youth purchasing behaviour. The article recommends that soft drinks companies should effectively utilise social media platforms, by adopting effective use of social media content through enhanced clarity and identity of content. Moreover, companies should capitalise on awareness opportunities created through ease of social media use and the level of knowledge of youths as means to recruit new consumers as well as retain existing ones.